Reduction of graft-versus-host disease in neonatal F1 hybrid mice. - DeGiorgi, L (1990)
Pre-immunization of BALB/c (H-2d) mothers with C57BL/10 (H-2b) or CBA/H (H-2k) spleen cells partially protected the F1 hybrid offspring of (BALB/c x C57BL/10) or (BALB/c x CBA/H) matings from graft-versus-host-disease (GVHD) induced by neonatal intraperitoneal inoculation with spleen cells of the paternal strain. The effects achieved were manifest as a reduction in mortality. Experiments to establish whether the phenomenon was antibody mediated were performed by passive pre-immunization of BALB/c mothers with alloantisera obtained from BALB/c previously immunized with C57BL/10 spleen cells. Alloantisera produced an equivalent reduction in GVHD mortality. Some of the F1 mice that survived challenge with paternal strain spleen cells were proven to be haemopoietic chimaeras using immunofluorescence with anti-MHC monoclonal antibodies and polymorphism of the enzyme glucose-phosphate-isomerase present in the strains used. The possible mechanisms of protection from GVHD in our mouse model are discussed.